(untitled) (Revista Archai, 2020)
Contemporary advanced technology seems to raise new and fundamental questions as it apparently provides a human subject with an infinite range of incoming possibilities. Accordingly, research on the implications of technology is massive and splits into hard critics and faithful supporters. Yet, technological activities cannot be defined in terms of their products alone. Indeed, every technological behaviour unfolds the very same tension against what would have been naturally impossible, in absence of that same behaviour. Thus, the debate on technology appears to be independent from any level of technological sophistication, and so its roots can be traced back in the dawn of Western thought. In this article, I argue that the faithful and sceptic views today at stake on hard-technology can be explained as a revival of the twofold attitude towards demons, developed in the history of Western thought. I show how demons have always embodied the human natural limits and the incomprehensible aspects of reality. Exactly as in the case of demons, hard-technology is now seen as a fearful destroyer of both nature understood as a complex system and human naturalness or as a trustful way to save humanity from decay, which complements what is naturally imperfect and, then, perfectible. Yet, none of these irreducible approaches opens a satisfactory path towards the solution of the contemporary issues on technology. On the contrary, by drawing upon ancient Greek neutral demonology the debate on technology may be definitively returned to its teleological and ethical dimension.